POST-TRAUMATIC STRESS DISORDER AND HEALTH PERSPECTIVE: VICTIMS OF MOTOR VEHICLE ACCIDENTS IN JORDAN - Al-Kofahy, Lilibeth (European Scientific Journal, ESJ, 2015)
Motor vehicle accident survivors who develop post-traumatic stress disorder have become an important health issue. Trauma resulting from Motor Vehicle Accidents has been attracting of increasing concern, with death from injuries is projected to reach 8.4 million in 2020 as compared to 5.1 million in 1990, particularly in developing countries including Jordan. A descriptive phenomenological approach was used for this study to identify and explore the lived experience of post-traumatic stress disorder of individuals who have been involved in a motor vehicle accident in Jordan. Seven themes were explicated from the participants’ transcripts of interview: feeling frustrated at a diminishing health status; struggling to maintain a state of independence; harboring feelings of not being able to recover; feeling discriminated against and marginalized by society; feeling ignored and neglected by health care professionals; feeling abandoned by family; moving toward acceptance through having faith in God. The current social services policies of the Jordanian Health Care System have given little credence to the health care needs of people with PTSD. As a result of this inattention, there is a noticeable lack of processes and protocols concerning care of the mentally ill and people with PTSD. The lack of policy direction has also led to a lack of health resources in this area including specialized clinics. Access to the limited services continues to place patients in vulnerable situations. Lack of policy direction has also impacted on access to health benefits. Presently, support of people with PTSD primarily falls to the family within Jordanian culture. Social support includes providing physical, emotional and financial assistance. Although change is taking place, it is slow and spasmodic.